PENGARUH PENGGUNAAN MEDIA AUGMENTED REALITY TERHADAP MINAT BELAJAR SENI BUDAYA SISWA DI SMPN 4 PALLANGGA - Muh. Sanjaya; Aco; Nurindah; Zulkifli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to analyze the influence of using Augmented Reality media on students' interest in learning arts and culture at SMPN 4 Pallangga. This research uses a quantitative approach with experimental methods and a pre-experimental design (one-shot case study). A total of 132 students from SMPN 4 Pallangga were involved in this research. The instruments used include questionnaires to measure the influence of Augmented Reality media and observations of learning interest.The results of the product moment correlation analysis through SPSS version 25 show the value of r = 0.99. The r value indicates that interest in learning is classified as a very strong correlation. Then H0 is rejected and Ha is accepted. The effect of Augmented Reality media value on learning interest is 98.01% and the remaining 01.99% is influenced by other variables not mentioned in the study. Based on calculations through the tcount formula with the provisions of the error rate ɑ = 0.05; df = N = 132 so that the ttable = 1.656 is obtained. It turns out that tcount> from ttable or 4.593>1.656. Then the correlation or relationship of Augmented Reality media with learning interest is significant.